Menggapai Inklusivitas: Menyingkap Kendala dan Tantangan di Sekolah Non-Inklusi dalam Menerima Anak Berkebutuhan Khusus - Filasofa, Lilif Muallifatul Khorida; Mursid; Rahmawati, Ika (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study explores the application of a holistic approach in improving the inclusion of children with special needs in non-inclusive schools, taking into account psychological, social, and academic aspects. Qualitative research was conducted through observation of interactions and behavior of children at RA Bina Mutiara Hati, Semarang. Interviews with the school principal and Class A teachers revealed the characteristics of children with special needs, the school's strategies, readiness to accommodate them, and the challenges faced in managing an inclusive environment. Documentation included observation notes, interview recordings, and photos to support the analysis. Descriptive analysis techniques were used to interpret the data in a structured manner. The research results showed obstacles such as inadequate infrastructure, limited teacher training, and a lack of support from parents and the community. It was found that coordination between schools, parents, and the community plays an important role in overcoming the challenges of inclusive education. Recommendations include improving school facilities, providing ongoing training for teachers, and launching community awareness campaigns. Additionally, parental involvement in creating an inclusive educational environment is strongly emphasized. This study is expected to assist non-inclusive schools in providing more responsive services to the needs of children with special needs and in addressing various existing challenges.